A study on the impact of the quality of management education on the new economy-knowledge: Evidence from members of OIC countries - Maryam Yokhaneh; Rafik Baghoumian (Management Science Letters)
This paper studies the effects of Quality of Management Education (QME) at universities on knowledge creation, application and distribution in knowledge based economy(KEI). The study also investigates the influence of QME on effective use of knowledge in economic development(KI).Using some regression technique, the study has determined a positive relationship of the effects of QME on KEI and KI in members of organization of Islamic cooperation (OIC). In addition, the study investigates the position of Iran in terms of quality of management education and the level of knowledge based economy.